Fibre-Reinforced Geopolymer Composites - Ahmed, Shaikh (Woodhead publications, 2013)
Concrete is brittle and has low tensile and flexural strength and strain capacity. Fibres make it ductile or quasi- ductile with improved tensile and flexural strength, strain capacity, toughness and energy absorption. The binder in fibre- reinforced cement composites (FRCCs) is mainly Portland cement. Environmental awareness in the construction industry is promoting alternative binders to reduce the amount of CO 2 released. The binders in FRCCs can be replaced with inorganic binders, called geopolymeric cement, to create fibre- reinforced geopolymer composites (FRGCs), which are greener. This chapter discusses mechanical properties for FRGCs reinforced with short fibres. Ductile fibre- reinforced geopolymer composites (DFRGCs) exhibiting strain hardening and multiple cracking in flexure are presented.